Sustained Inflammatory Signalling through Stat1/Stat2/IRF9 Is Associated with Amoeboid Phenotype of Melanoma Cells - Gandalovičová, Aneta; Šůchová, Anna-Marie; Čermák, Vladimír; Merta, Ladislav; Rösel, Daniel; Brábek, Jan (Cancers, 2020)
The invasive behaviour of cancer cells underlies metastatic dissemination; however, due to the large plasticity of invasion modes, it is challenging to target. It is now widely accepted that various secreted cytokines modulate the tumour microenvironment and pro-inflammatory signalling can promote tumour progression. Here, we report that cells after mesenchymal-amoeboid transition show the increased expression of genes associated with the type I interferon response. Moreover, the sustained activation of type I interferon signalling in response to IFNβ mediated by the Stat1/Stat2/IRF9 complex enhances the round amoeboid phenotype in melanoma cells, whereas its downregulation by various approaches promotes the mesenchymal invasive phenotype. Overall, we demonstrate that interferon signalling is associated with the amoeboid phenotype of cancer cells and suggest a novel role of IFNβ in promoting cancer invasion plasticity, aside from its known role as a tumour suppressor.
Keywords: invasion; inflammation; interferon; plasticity; mesenchymal; amoeboid; melanoma